"Nicht mitmachen!" and "Weitermachen!": Rereading Adorno and Marcuse on Theory and Praxis. Issue 1 (2nd January 2022) - Della Torre, Bruna; Altheman, Eduardo
Abstract : This essay discusses the relation between Theodor W. Adorno and Herbert Marcuse, with their dialogue on the political events of the 1960s student movements as its main axis. While these two critical theorists are usually taken as antithetical in their positions regarding this issue, the essay problematizes such a dualist conception by resorting not only to their theoretical works but also to their unpublished correspondence and other public interventions. The aim is to contextualize such texts and letters to present a more complex view of the debate in question.